Socioeconomic Disparities in Infant Mortality: Evidence from the 2017 Indonesia Demographic and Health Survey - Yuniar Wardani; Ichtiarini Nurullita Santri; Suci Musvita Ayu; Liena Sofiana; Asa Ismia Bunga Aisyahrani; Mochamad Iqbal Nurmansyah; Moh. Irma Sukarelawan (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2025)
Introduction: Indonesia did not meet the MDGs and SDGs targets. Factors contributing to the reduction of infant mortality in Indonesia in the last decade need to be understood. Methods: This cross-sectional study uses a dataset from the 2017 Indonesia Demographic and Health Survey (IDHS). The sample size is 3413 infants. Multiple logistic regression results are performed by odds ratio (OR). Results: Infants living in the middle wealth index were at higher risk of infant death compared to infants with the poorest and poor counterparts (AOR=1.73; 95% CI=1.14 2.61). The risk of infant death was almost two times higher among infants who were born in Sumatera (AOR=1.83; 95% CI=1.02 3.27), Java and Bali (AOR=2.14; 95% CI=1.21 3.76), and Sulawesi (AOR=2.39; 95% CI=1.15 4.96) than infants who were born in Papua and Maluku. Conclusion: Infants living in the middle wealth index, Sumatera, Java and Bali, and Sulawesi had a higher mortality risk than others.